Gubbubu

Visszahelyettesítve ezt az első egyenlet (*)-gal megjelölt formájába:
 
:: <math> m^{2} </math> &nbsp; <math> = </math> <math> b^{2}-x^{2} </math> <math> = </math> &nbsp; <math> b^{2} - \left( \frac{ -a^{2} + b^{2} + c^{2} }{2c} \right) ^{2} </math> &nbsp; <math> = </math> &nbsp; <math> b^{2} - \frac{ \left( -a^{2} + b^{2} + c^{2} \right) ^{2} }{ \left( 2c \right) ^{2} } </math> &nbsp; <math> = </math> &nbsp; <math> b^{2} - \frac{ \left( -a^{2} + b^{2} + c^{2} \right) ^{2} }{ 4c^{2} } </math> &nbsp; <math> = </math> <br> <math> = </math> &nbsp; <math> \frac { 4c^{2} \cdot b^{2} } { 4c^{2} } - \frac{ \left( -a^{2} + b^{2} + c^{2} \right) ^{2} } { 4c^{2} } </math> &nbsp; <math> = </math> &nbsp; <math> \frac { 4b^{2} c^{2} - \left( -a^{2}+b^{2}+c^{2} \right) ^{2} } { 4c^{2} } </math> &nbsp; <math> = </math> &nbsp; <math> \frac { \left( 2bc \right) ^{2} - \left( -a^{2}+b^{2}+c^{2} \right) ^{2} } { \left( 2c \right) ^{2} } </math> &nbsp; <math> = </math> &nbsp; <br> <math> = </math> <math> \frac { \left( 2bc \right) ^{2} - \left( -a^{2}+b^{2}+c^{2} \right) ^{2} } { \left( 2c \right) ^{2} } </math> &nbsp; <math> = X </math>.
 
Alkalmazva a nevezetes <math> A^{2} - B^{2} = \left( A+B \right) \left( A-B \right) </math> azonosságot az <math> A = 2bc </math> és <math>B = -a^{2}+b^{2}+c^{2} </math> esetekre;
 
:: <math>X</math> &nbsp; <math>=</math> &nbsp; <math> \frac { \left[ \left( 2bc \right) + \left( -a^{2}+b^{2}+c^{2} \right) \right] \left[ U \right] } { W } </math>